2017
DOI: 10.1002/mus.25743
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal community walking activity in Duchenne muscular dystrophy

Abstract: Community ambulation data provide valid and sensitive real-world measures that may inform clinical trials. Muscle Nerve 57: 401-406, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 31 publications
4
37
0
Order By: Relevance
“…With advances in technology, new therapies will probably be assessed increasingly through activity monitoring in combination with measurements of new, clinically meaningful biomarkers. 127 Robotics and other rapid advances in technology will improve independence, participation, and quality of life. Emerging therapies such as dystrophin-restorative therapies might improve exercise or activity capacity and safety.…”
Section: Discussionmentioning
confidence: 99%
“…With advances in technology, new therapies will probably be assessed increasingly through activity monitoring in combination with measurements of new, clinically meaningful biomarkers. 127 Robotics and other rapid advances in technology will improve independence, participation, and quality of life. Emerging therapies such as dystrophin-restorative therapies might improve exercise or activity capacity and safety.…”
Section: Discussionmentioning
confidence: 99%
“…The relationships identified between TPA mins and KEMVC in BMD are furthered by the stronger relationship of TPA mins with 10 m walk time in ambulant MD participants and are consistent with those relationships identified within elderly populations 24,70 and paediatric DMD populations. 58 However, future work is required to quantify activity thresholds relative to separate conditions, and between ambulant and non-ambulant individuals, in order to quantify PA intensities, and the relative intensities relationships with functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The four participants to not perform the 10 m walk did so at their own request due to safety concerns. The 10 m walk was performed on an even, carpeted surface and is a common measure of function within neuromuscular conditions . All participants started in a standing position and were instructed to walk as quickly and safely as they could, with the time recorded from the point of ‘Go’ from the practitioner to the point of crossing the finish line.…”
Section: Methodsmentioning
confidence: 99%
“…Accelerometers have been shown to be useful in monitoring gait (eg, overall physical activity level, step activity and gait alterations) in boys with DMD and in children with other neurological diseases . Most of the experience with the use of accelerometers in the UEs is in adult patients with stroke and multiple sclerosis .…”
Section: Introductionmentioning
confidence: 99%
“…12 Accelerometers have been shown to be useful in monitoring gait (eg, overall physical activity level, step activity and gait alterations) in boys with DMD and in children with other neurological diseases. [13][14][15][16][17][18][19][20][21] Most of the experience with the use of accelerometers in the UEs is in adult patients with stroke and multiple sclerosis. [22][23][24][25] Uswatte et al 26 showed that if complementary self-reported measures are used simultaneously they can provide rich information about UE activities.…”
Section: Introductionmentioning
confidence: 99%